Oral history in UK doctoral research: extent of use and researcher preparedness for emotionally demanding work - Calabria, Verusca; Harding, Jenny; Meiklejohn, Louise (Taylor and Francis Group, Routledge, 2023)
Oral history is increasingly used in academic teaching and research across many disciplines and contexts in the UK. However, there is currently no accurate picture of the extent to which oral history is practiced at the doctoral level and the diversity of its disciplinary and institutional contexts. Similarly, there is no clear understanding of how doctoral students are prepared for doing oral history research and what their particular concerns might be. This article presents the findings from a recent mixed-method pilot study which explored (1) the extent of use of oral history in doctoral research both as a main methodology and a supplementary method of data collection, and (2) the conceptual, ethical, and practical needs of doctoral students engaging with oral history. Focus group interviews generated detailed discussion of the often-unrecognized emotional labor involved in oral history research, the lack of preparedness in dealing with it, its potential impact on the researcher, and ways of mitigating this. This article examines the underinvestigated element of emotional labor in conducting oral history research, entanglements of responses and responsibilities, and ways of practicing an ethics of care in the current higher education context.